(untitled) (Ustozlar uchun, 2025)
This article examines the scientific and pedagogical foundations of teaching language to young children. It analyzes the factors influencing speech development in preschool-aged children, the main principles of language teaching, and ways of applying them in practice. The article highlights the importance of considering children’s age and individual characteristics, organizing instruction based on play activities, and using a communication-oriented approach. The research findings are of methodological value for preschool educators and teachers.